A decision-making process to support public administrations in defining local energy policies. (June 2018) - Vergerio, Giulia; Becchio, Cristina; Delmastro, Chiara; Lanzini, Andrea; Corgnati, Stefano P.; Borchiellini, Romano
Highlights: A decision-making process for public administrations is introduced. The proposed methodology aims to define local energy policies on public buildings. Key performance indicators and quadrants-chart are proposed as energy-policy tools. The Energy Center Initiative is involved in supporting Torino's Municipality energy policies. Overcoming data gathering barriers is crucial in defining local energy policies. Abstract: In all world regions urbanisation growth is expected to continue to 2050 and consequently urban areas have a key role in the transition to a more sustainable future. To reduce cities footprint, long-term strategies involving actions across all the main urban sectors (buildings, transport, industry and supply) are required. Therefore, methodologies that support public administrations in their decision-making planning process are of key importance. The research is focused on the necessity of re-thinking cities intervening on existing buildings and, consequently, on the urgent requirement to develop local energy policies able to encourage the spreading of energy efficiency measures, lowering some barriers to the interventions. Consistently, the main goal of the research here reported is to develop a methodology as support to the decision making process in defining local energy policies. This methodology aims to suggest, by means of specifically identified tools (Key Performance Indexes, quadrant-charts, Reference Buildings, etc.) and evaluation approaches (cost-optimal analysis, cost-benefits analysis, etc.), local policies of energy planning related firstly to public buildings. The present paper provides a full accounting, with some preliminary results, of the methodology implementation and its application to the case study of the Municipality of Torino, since a collaboration between it and the Politecnico of Torino is ongoing in the framework of the Energy Center Initiative. This first ongoing application enables to test the methodology and to highlights the necessity of strengthen the cooperation among municipal offices and to develop mechanism for sharing data such as digital achieves.